PENDAMPINGAN PENGUATAN STRATEGI PEMASARAN SUSU KAMBING PADA EL FITRA FARM DI KOTA PADANG - Fitrimawati; Ida Indrayani; Hilda Susanty (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
EL Fitra Farm dairy goat farm, located in Padang City. It is the largest dairy goat farm in terms of population in the city. The farm demonstrates excellent technical performance. The breeds raised at the farm include Sapera, Anglo Nubian, Anglo Sapera, and Anglo Saperaboer. The goats are fed fermented green fodder and legumes. The average milk production is approximately 1.5 liters per goat per day. Milking is performed using a milking machine. The main objective of this community service was to optimize the marketing strategy of EL Fitra Farm’s goat milk products. The methods used included lectures, discussions, and mentoring. The implementation stages involved identifying problems and potential opportunities with partners, followed by mentoring in the development of marketing strategies. The marketing strategies were developed to suit the specific conditions of the partner, using the marketing mix (4Ps) approach: Product, Price, Place, and Promotion. The strategies were formulated based on a SWOT analysis by aligning identified strengths, weaknesses, opportunities, and threats. S-O Strategy: Increase production volume, create marketing content, establish milk distribution partnerships, and expand the market reach. W-O Strategy: Develop product variations, design user-friendly and storable packaging, establish a brand, introduce different packaging sizes and pricing, engage resellers, participate in exhibitions and bazaars, use social media marketing, sell products at public sports venues, and obtain certificates of consumption suitability. S-T Strategy: Identify and create new market segments. W-T Strategy: Obtain halal certification and laboratory test results, invest in machinery and production technology, and offer price discounts.